Conduction disease in cardiac amyloidosis patients: A case series suggesting a role for left bundle branch area pacing - Ojas H. Mehta; Keyrian Louis Le Gratiet; Markus Sikkel; Laurence D. Sterns (Indian Pacing and Electrophysiology Journal)
Transthyretin Cardiac amyloidosis (ATTR-CA) is an increasingly recognised cause of heart failure in our elderly patients with preserved ejection fraction. Patients with ATTR-CA who require permanent pacemaker implantation often have preserved ejection fraction and do not meet the clinical indication for cardiac resynchronization therapy (CRT). In these patients, left bundle branch area pacing (LBBAP) can be a reasonable option to maximise physiological activation of the left ventricle. We describe a series of three patients with cardiac amyloidosis who have undergone LBBAP with the use of lumenless leads and successful capture of the myocardium and left bundle branch region.